2009
DOI: 10.1177/000348940911800509
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus—Associated Oropharyngeal Squamous Cell Carcinomas: Primary Tumor Burden and Survival in Surgical Patients

Abstract: Primary tumor burden was not associated with HPV status. Patients with HPV-positive oropharyngeal squamous cell carcinomas had a higher prevalence of neck nodal metastases and high-grade lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…These virally mediated cancers tend to present with smaller primary tumor volume and more advanced nodal disease. 21,26,27 This changing pattern of the disease with fewer locally advanced tumors may then be more amenable to surgical resection without rendering patients functionally disabled from high-volume resections. Indeed, of the 364 patients (88.8%) in this study treated for oropharyngeal primary tumors, 314 had pathologic stage T2 or lower disease.…”
Section: Discussionmentioning
confidence: 99%
“…These virally mediated cancers tend to present with smaller primary tumor volume and more advanced nodal disease. 21,26,27 This changing pattern of the disease with fewer locally advanced tumors may then be more amenable to surgical resection without rendering patients functionally disabled from high-volume resections. Indeed, of the 364 patients (88.8%) in this study treated for oropharyngeal primary tumors, 314 had pathologic stage T2 or lower disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrary to the common misconception that HPV and smokingrelated carcinogenesis pathways are either partially or totally exclusive of each other. The larger literature also shows most HPV-related OSCC patients to be current or former smokers [2,8,[35][36][37][38][39], although it is clear that there are less overall smokers amongst the HPV-related cases and their amounts of exposure are less. Dysplastic changes secondary to tobacco smoke could be accompanied by aberrant expression of B7-H1.…”
Section: Discussionmentioning
confidence: 99%
“…The younger age of patients with HPV-related tumors, the lower smoke and alcohol exposure rates, and increased rates of sexual exposure suggest that HPV has a central role in carcinogenesis [1][2][3][4]. The prevalence of HPV in OSCC is between 60 % and 80 %, and rates are steadily increasing, with the mechanism believed to be chronic persistent infection leading to carcinogenesis [5][6][7][8]. Studies have demonstrated that oral infection by HPV is not uncommon [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies found that HPV status also conferred a favorable prognosis in surgically treated oropharyngeal cancer patients (31, 40). However, a recent study from the Mayo Clinic showed that HPV status did not impact prognosis in patients presenting with surgically resectable cancers of the oropharynx (41). In this latter study, the association between HPV status and overall survival had a hazard ratio of 1.02 (the 95% CI: 0.53–1.99).…”
Section: Discussionmentioning
confidence: 99%